Stunting prevention: how to differentiate stunting and short stature. A community service webinar with aisyiyah regional leader in malang - Pertiwi Febriana Chandrawati; Akbari Agung Nusantara (DokTIn MEDIKA Jurnal Pengabdian Masyarakat, 2022)
Background: The issue of stunting and short stature continues to receive attention from the Indonesian government because it will determine the quality of Indonesian Human Resources in the future. Stunting is short, but short is not necessarily stunting. Stunting is a condition of failure to thrive due to malnutrition in the first thousand days of a child's life.Short-stature is at risk of stunting if the problem is not immediately resolved. Protein intake from animal meat is playing as an essential role in preventing stunting. Purpose: The program aims to increase the knowledge of the Aisyiyah regional leader in Malang in distinguishing between short stature and stunting and how to prevent it. Method: We conducted a seminar online using the pandemic COVID-19-prevention-protocol. Participantsasked questions and discussedthis topic. Conclusion: A working group program and pocketbook in stunting prevention in children as a collaboration between the medical faculty of the University of Muhammadiyah Malang, the regional leader of Aisyiyah Malang, and Dewan Pimpinan Wilayah of Muhammadiyah advisor will be formed. .